2017
DOI: 10.1016/j.socscimed.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Switching to sanitation: Understanding latrine adoption in a representative panel of rural Indian households

Abstract: Open defecation, which is still practiced by about a billion people worldwide, is one of the most compelling examples of how place influences health in developing countries. Efforts by governments and development organizations to address the world’s remaining open defecation would be greatly supported by a better understanding of why some people adopt latrines and others do not. We analyze the 2005 and 2012 rounds of the India Human Development Survey (IHDS), a nationally representative panel of households in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 30 publications
5
44
2
Order By: Relevance
“…Although these factors are significantly associated with open defecation in the region, the magnitudes of these associations are small relative to that of religion and open defecation. This finding aligns with recent evidence that economic, education, demographic, and home improvement changes only weakly explain latrine adoption in rural India between 2005 and 2012 (Coffey, Spears, & Vyas, 2017b). …”
Section: Discussionsupporting
confidence: 89%
“…Although these factors are significantly associated with open defecation in the region, the magnitudes of these associations are small relative to that of religion and open defecation. This finding aligns with recent evidence that economic, education, demographic, and home improvement changes only weakly explain latrine adoption in rural India between 2005 and 2012 (Coffey, Spears, & Vyas, 2017b). …”
Section: Discussionsupporting
confidence: 89%
“…Given these findings, a solution which brings the supposed benefits of sedentarisation (primarily access to health care) without the negative health outcomes associated with permanent camps is far more preferable. As has been pointed out by Coffey et al (2017) the social and cultural context is crucial when trying to understand and bring about change in sanitation behaviour.…”
Section: Cultural Relevance Of Health Infrastructurementioning
confidence: 99%
“…Jenkins et al suggested that 37% of households were willing to install toilets in Ghana [13]. Coffey et al observed income, education, and improved housing could affect the attitude of rural Indian households to use in toilets [14]. Lamichhane et al suggested that more than 60% of respondents were willing to pay for toilets in Hawaii and observed that gender, age, and income could affect the respondents' attitudes [15].…”
Section: Literature Reviewmentioning
confidence: 99%